Efforts to achieve sustainable competitive advantage for SMEs: The strategic entrepreneur model - Widodo; Widyo, Dandri (The Economics and Finance Letters, 2024)
The aim of this research is to examine and analyze the dimensions of strategic entrepreneurship that are able to realize long-term sustainable competitive advantage in small and medium businesses. This research methodology and sampling technique use a purposive sampling method, with a total of 150 respondents from Batik Small and Medium Enterprises industry leaders in Central Java Province, Indonesia. Then the analysis technique uses Structural Equation Modeling (SEM) with AMOS software. Empirical data supports the six hypotheses proposed in this study. Specifically, the first hypothesis is that entrepreneurial culture is influenced by entrepreneurial learning. The second hypothesis posits that entrepreneurial culture influences entrepreneurial capacity. The third entrepreneurial learning hypothesis is influencing entrepreneurial capacity. The four entrepreneurial capacities are influencing sustainable competitive advantage. The fifth hypothesis is that entrepreneurial learning influences a sustainable competitive advantage. The sixth hypothesis is that entrepreneurial culture influences a sustainable competitive advantage. The practical implication for realizing sustainable competitive advantage for batik Small and Medium Enterprises in Central Java Province, Indonesia, is to improve and develop entrepreneurial learning built by indicators 1). Experience 2). Cognitive; 3). Network; 4). Social relationships. Entrepreneurial learning and entrepreneurial capacity can mediate entrepreneurial culture towards sustainable competitive advantage. The strategic entrepreneurship development model begins with the establishment and enhancement of an entrepreneurial culture, which encompasses the following elements: 1). Enthusiasm 2). Stakeholder alignment 3). Learning and Development Support. 4). Change is driven by business opportunities.